METALINGUISTIC SKILLS AND LANGUAGE USE IN THE PROPOSITIONS OF FOUR BRAZILIAN SIGN LANGUAGE CURRICULA - Barbosa, Felipe Venâncio (Momento - Diálogos em Educação, 2022)
This paper presents a description of the general aspects of four Libras curricula developed by the municipalities in the state of Rio Grande do Sul and the state of São Paulo - Rio Grande, Canoas, Guarulhos and São Paulo, in Brazil. The propositions for Libras are presented in these documents and an analysis is made of how they approach metalinguistic skills and language use. The analyzed documents reflect a direction pointed out by deaf studies and by current linguistic studies regarding the deepening of the objectives of teaching sign languages ​​as a first language. The relationship between the objectives of learning and development aiming at use and metalanguage revealed a preponderance of those focusing on metalinguistic skills in two of the documents. The peculiarities of these four documents make them different, though in line with the Brazilian Common National Curricular Base when carrying out their propositions according to their local realities without leaving aside the guidelines of the federal document and the state of the art in the area.